Laser‐Assisted Lattice Recovery of Graphene by Carbon Nanodot Incorporation. Issue 52 (22nd November 2019) - Borenstein, Arie; Strauss, Volker; Kowal, Matthew D.; Anderson, Mackenzie; Kaner, Richard B.
Abstract: Producing highly oriented graphene is a major challenge that constrains graphene from fulfilling its full potential in technological applications. The exciting properties of graphene are impeded in practical bulk materials due to lattice imperfections that hinder charge mobility. A simple method to improve the structural integrity of graphene by utilizing laser irradiation on a composite of carbon nanodots (CNDs) and 3D graphene is presented. The CNDs attach themselves to defect sites in the graphene sheets and, upon laser‐assisted reduction, patch defects in the carbon lattice. Spectroscopic experiments reveal graphitic structural recovery of up to 43% and electrical conductivity four times larger than the original graphene. The composites are tested as electrodes in electrochemical capacitors and demonstrate extremely fast RC time constant as low as 0.57 ms. Due to their low defect concentrations, the reduced graphene oxide‐carbon nanodot (rGO‐CND) composites frequency response is sufficiently fast to operate as AC line filters, potentially replacing today's electrolytic capacitors. Using this methodology, demonstrated is a novel line filter with one of the fastest capacitive responses ever reported, and an aerial capacitance of 68.8 mF cm −2 . This result emphasizes the decisive role of structural integrity for optimizing graphene in electronic applications. Abstract : Carbon nanodots (CNDs) are added to graphene in order to enhance its properties by lowering its concentration of defects. The CNDs attach themselves to defect sites in the graphene sheets and, upon laser‐assisted reduction, patch defects in the carbon lattice. Spectroscopic experiments reveal graphitic structural recovery up to 43% and electrical conductivity improvement up to 400%.